Changing lives: stratified medicine in monogenic diabetes - Hattersley, Andrew (Henry Stewart Talks, 2015)
Approaches to diabetes treatment, Maturity onset diabetes of the young (MODY) in the pre-genetic era, MODY in the pre-genetic era, Treatment in glucokinase MODY, Treatment in HNF1a MODY, Renal cysts and diabetes (RCAD) syndrome and its treatment, The diagnosis of MODY in pediatric clinics, MODY probability calculator, Neonatal diabetes (ND), The role of Kir6.2 and SUR1 mutation in ND, Testing for ND, Using Mice model to learn on pancreatic development and ND, Pancreatic agenesis and patients' genetics, Mutations in PTF1A mutations and pancreatic agenesis